Exploration of Digital Creativity: Construction of the Multiteam Digital Creativity Influencing Factor Model in the Action Phase - Zhang, Jing; Chen, Weilong; Xiao, Yuchun; Wang, Baohua (Frontiers in Psychology, 2022)
Based on MTS theory and creativity theory, this study explores the influencing factor model of multiteam digital creativity (MTDC) in the action phase through two cross-validation studies, filling a theoretical gap and responding to the research call. Study 1 is a qualitative analysis method to fully explore the relevant influencing factors and enhance the theoretical saturation. Study 2 is an optimized DEMATEL method, known as the CL-WG DEMATEL analysis method, which cross-validates the new theoretical model and measures the centrality of the influencing factors. This study finds that the influence factor model of MTDC has eight major factors and distributes in four different levels. Further analysis shows that the three influences (team digital ability, multiteam digital sharing, and organizational digital resource matching) with the highest centrality of impact on MTDC all belong to the collective level, which indicates the uniqueness of the action phase of the performance episodes. The two cross-validation studies enhance the scientific validity of the new theoretical exploration. In addition, Theoretical and practical implications of the results are presented, and future directions for research are discussed.